1987
DOI: 10.1017/s030500090001271x
|View full text |Cite
|
Sign up to set email alerts
|

The eyes have it: lexical and syntactic comprehension in a new paradigm

Abstract: A new method to assess language comprehension in infants and young children is introduced in three experiments which test separately for the comprehension of nouns, verbs, and word order. This method requires a minimum of motor movement, no speech production, and relies on the differential visual fixation of two simultaneously presented video events accompanied by a single linguistic stimulus. The linguistic stimulus matches only one of the video events. In all three experiments patterns of visual fixation fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
367
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 522 publications
(376 citation statements)
references
References 27 publications
3
367
0
6
Order By: Relevance
“…Gender was thus not included in the main analyses. Past literature has suggested that when testing young children on multiple trials, first-trial performance would be less biased by confounding factors (e.g., learning effect, fatigue, or perseveration) and thus the most convincing (Golinkoff, Hirsh-Pasek, Cauley, & Gordon, 1987;O'Sullivan, Mitchell, & Daehler, 2001;Schmitt & Anderson, 2002;Suddendorf, 2003). Therefore, each set of the analyses below examined children's performance (a) on the first trial and (b) over the four trials.…”
Section: Resultsmentioning
confidence: 99%
“…Gender was thus not included in the main analyses. Past literature has suggested that when testing young children on multiple trials, first-trial performance would be less biased by confounding factors (e.g., learning effect, fatigue, or perseveration) and thus the most convincing (Golinkoff, Hirsh-Pasek, Cauley, & Gordon, 1987;O'Sullivan, Mitchell, & Daehler, 2001;Schmitt & Anderson, 2002;Suddendorf, 2003). Therefore, each set of the analyses below examined children's performance (a) on the first trial and (b) over the four trials.…”
Section: Resultsmentioning
confidence: 99%
“…After training, infants were presented with a single word and two potential referents, the cross-trial correct referent and a foil. Past research (e.g., Golinkoff, Hirsh-Pasek, Cauley, & Gordon, 1997;Swingley & Aslin, 2000) shows that within this kind of preferential looking task, infants look longer at the labeled test object. Thus if infants have calculated the statistics appropriately, despite the uncertainty on individual learning trials, they should look longer at the correct referent of the word form.…”
Section: Introductionmentioning
confidence: 92%
“…7 Note that 7% may be unnecessary; an even lower amount may be adequate if the raising of nite verbs is established before the two word stage, which could be con rmed by comprehension studies such as the preferential looking procedure (Golinkoff et al 1987).…”
Section: Frequency and Parameter Settingmentioning
confidence: 99%